Pemberdayaan usaha ekonomi produktif bagi masyarakat di Kelurahan Allepolea, Kecamatan Lau, Kabupaten Maros - M. Ikhwan Maulana Haeruddin; Abdul Hakim (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This activity aims to provide counseling and training on entrepreneurship and processing of products that produce economic value products, namely soap and detergent, as well as knowing marketing methods. The target participants of this activity are residents in Allepolea District, Lau District in Maros Regency. In general, participants were very enthusiastic about participating in the training, which was shown from their diligence and discipline in following each stage of the activity. In addition, each participant participates in determining training materials related to the implementation of the tasks performed every day. Each participant can produce products of economic value and can also market these products through an offline and online sales mechanism. Through this activity each participant feels the benefits of empowering productive economic business activities through activities and hopes that activities like this can be given regularly and also bring new assets to their knowledge and skills so that it will improve the lives of citizens economically.